2003
DOI: 10.1063/1.1545166
|View full text |Cite
|
Sign up to set email alerts
|

Sensors for sub-ppm NO2 gas detection based on carbon nanotube thin films

Abstract: Carbon nanotubes (CNTs) deposited by plasma-enhanced chemical vapor deposition on Si3N4/Si substrates have been investigated as resistive gas sensors for NO2. Upon exposure to NO2, the electrical resistance of the CNTs was found to decrease. The maximum variation of resistance to NO2 was found at an operating temperature of around 165 °C. The sensor exhibited high sensitivity to NO2 gas at concentrations as low as 10 ppb, fast response time, and good selectivity. A thermal treatment method, based on repeated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
248
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(263 citation statements)
references
References 11 publications
5
248
2
1
Order By: Relevance
“…However, a limitation in improving the sensitivity of the sensors is that many different gases in the ppb range can contribute to the response of the sensors, thereby deteriorating their selectivity. Improving the sensitivity of the sensors without sacrificing selectivity can be overcome by functionalisation, in many cases through controlling the composition (Gaury et al 2013) and structure (Franke et al 2006;Julien et al 2014;Valentini et al 2003) of the sensing materials at the nanometre scale -a branch of research that drives the material science community at the moment. .…”
Section: The Challengesmentioning
confidence: 99%
“…However, a limitation in improving the sensitivity of the sensors is that many different gases in the ppb range can contribute to the response of the sensors, thereby deteriorating their selectivity. Improving the sensitivity of the sensors without sacrificing selectivity can be overcome by functionalisation, in many cases through controlling the composition (Gaury et al 2013) and structure (Franke et al 2006;Julien et al 2014;Valentini et al 2003) of the sensing materials at the nanometre scale -a branch of research that drives the material science community at the moment. .…”
Section: The Challengesmentioning
confidence: 99%
“…Studies show that the graphene and CNTs and GNRs are good gas sensors. Experimental data have shown that the transport properties of nanotube changes upon exposure to gas molecules such as the O 2 , NO 2 , and NH 3 molecules [2,[4][5][6][7][8]. Experimental and theoretical studies of gas molecule adsorption on the graphene surface have been reported already [9][10][11][12][13][14][15][16] showing that H 2 O, NO, CO, NO 2 , and NH 3 molecules are physically adsorbed on the graphene.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid progress and improvement of nanotechnology, sensors fabricated by using carbon nanotubes (CNTs) as the sensing element were reported to give electrical response to different chemicals, such as NO 2 , NH 3 , CO, H 2 , and O 3 for gas detection [4][5][6][7][8][9]. CNT sensors provide high sensitivity, low power, and portable tools for in situ chemical analysis.…”
Section: Introductionmentioning
confidence: 99%